2018
DOI: 10.1183/13993003.01254-2018
|View full text |Cite
|
Sign up to set email alerts
|

Investigating unilateral pleural effusions: the role of cytology

Abstract: The vast majority of undiagnosed unilateral pleural effusions have fluid sent for cytological analysis. Despite widespread use, there is uncertainty about its sensitivity to diagnose malignant pleural effusions (MPEs). Our aim was to ascertain the utility of cytology using a large prospective cohort.Consecutive patients presenting with an undiagnosed unilateral pleural effusion were recruited to this UK-based study. All had pleural fluid sent for cytological analysis. Cytological sensitivity was based on the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(93 citation statements)
references
References 33 publications
(37 reference statements)
1
79
0
1
Order By: Relevance
“… * Information from references 4, 10, 12, 25, 28, 31, 38, 40, 44, 52 and 53. $ For labeling mesothelioma. ‡ For distinguishing malignant from benign mesothelial proliferations. § For non-small cell lung cancer. ADA, adenosine deaminase; CEA, carcinoembryonic antigen; CT, computed tomography; EGFR, epidermal growth-factor receptor; FISH, fluorescence in situ hybridization; ICC, immunocytochemistry; NT-proBNP, amino-terminal fragment of probrain natriuretic peptide; PF, pleural fluid; S−PF, serum minus pleural fluid levels. …”
Section: Resultsmentioning
confidence: 99%
“… * Information from references 4, 10, 12, 25, 28, 31, 38, 40, 44, 52 and 53. $ For labeling mesothelioma. ‡ For distinguishing malignant from benign mesothelial proliferations. § For non-small cell lung cancer. ADA, adenosine deaminase; CEA, carcinoembryonic antigen; CT, computed tomography; EGFR, epidermal growth-factor receptor; FISH, fluorescence in situ hybridization; ICC, immunocytochemistry; NT-proBNP, amino-terminal fragment of probrain natriuretic peptide; PF, pleural fluid; S−PF, serum minus pleural fluid levels. …”
Section: Resultsmentioning
confidence: 99%
“…Diagnosing an MPE through PF poses some challenges. Historically, PF cytology yields were suggested to be 60%; however, more recent data would suggest that this is likely an overestimation [13,[47][48][49]. It is suggested that 50-75 mL should be sent as a minimum to maximise yield and a repeat fluid cytology may increase the yield by a further 26%, though this latter claim is based on a small retrospective series [50,51].…”
Section: Pleural Fluid Cytologymentioning
confidence: 99%
“…There exists a heterogeneity for yield, varying according to underlying tumour type. Typically, ovarian and breast cancer have a high diagnostic yield in PF (94.7% and 70.7%, respectively), lung adenocarcinoma fares the best of the lung cancers (82%), whilst mesothelioma fares particularly poorly (6.1%) [47].…”
Section: Pleural Fluid Cytologymentioning
confidence: 99%
“…withdrawn during thoracentesis and processed for cytology. The approximate overall cytological yield in MPE is a disappointing 50%, a number that can exceed 80% in exfoliative cancers such as ovarian adenocarcinoma and can fall under 30% in non-exfoliative cancers such as SCC [8,9]. It…”
Section: Resultsmentioning
confidence: 99%